USER BEHAVIOUR ON SPESIFIC ENVIRONMENT IN BOGOR BOTANICAL GARDEN - Andi Gunawan; Prita Indah Pratiwi (ASEAN Journal on Hospitality and Tourism, 2015)
Bogor Botanical Garden is one of well-known tourism destination in West Java,Indonesia, visited by various users around the world. The increase in demand fornature-based tourism also becomes a trend in urban society. People needs a comfortable, healthy, and sustainable living space to refresh from fatigue and recreate new experience relating to nature. Environmental behavior is crucial aspect raised by understanding (cognitive behavior) and assessment of physical quality of environment (affective behavior). In order to avoid environmental damage, it is necessary to observe the user behavior, to analyze the change of user behavior and formulate the guidelines for formal garden design. The study was conducted in three steps: site and behavior observation, behavior analysis, and recommendation. There was diversity of user behavior in Teysmann Garden in the morning and afternoon. This was driven by various perception and preference in the garden relating to personal and physical factors. The prominent activities in formal garden consisted of sitting, taking picture, and walking, while prominent settings intensively used were pavement lane, pergola, bench, and lawn. Abnormal action was found in lawn, monument, pergola, and bench. The prominent landscape elements or settings could be improved as main character in formal garden in achieving a good interaction between people and landscape as a basis for landscape sustainability of tourism destination area.